IKAN ARWANA SEBAGAI SUMBER IDE PENCIPTAAN KRIYA - Kasanah, Usfatun; Naam, Muh Fakhrihun (Eduarts: Jurnal Pendidikan Seni, 2024)
Carving motifs are one of the most important factors in creating a carving work, by taking sources of ideas from motifs of flora, fauna, and so on. The existence of various sources of ideas makes researchers interested in the shape of arowana fish and lotus flowers. Apart from being an ornamental fish which is almost extinct, no business people in Grobogan Regency yet use carved arowana fish motifs, most still use floral and tiger motifs. This research aims to understand the process of creating carvings and describe the results of the carving work with the source of ideas being arowana fish and lotus flowers. The method used in this research is a qualitative descriptive research method. The procedure for carrying out the research is to create a carving motif that takes the source of the idea from the arowana fish and its habitat, then realizing it in a carved work. Data collection techniques using field observations, interviews with carving craftsmen and artists, documentation. The results of the research by describing the carving work in the creation process on teak wood using carving techniques, as well as using spray paint coloring techniques using brown melamine paint, the resulting work shows that it is suitable to be used as a carving motif and needs to be developed in various attractive colors and shapes. If a product is marketed, it is best if there is a motif that can be highlighted, if the motif is left like that, the motif will seem monotonous